Membrane-camouflaged biomimetic nanoparticles as potential immunomodulatory solutions for sepsis: An overview - Wang, Yanbei; Liu, Liping; Zheng, Xinchuan; Liu, Xin (Frontiers in Bioengineering and Biotechnology, 2023)
Sepsis is a life-threatening organ dysfunction due to dysregulated host responses induced by infection. The presence of immune disturbance is key to the onset and development of sepsis but has remarkably limited therapeutic options. Advances in biomedical nanotechnology have provided innovative approaches to rebalancing the host immunity. In particular, the technique of membrane-coating has demonstrated remarkable improvements to therapeutic nanoparticles (NPs) in terms of tolerance and stability while also improving their biomimetic performance for immunomodulatory purposes. This development has led to the emergence of using cell-membrane-based biomimetic NPs in treating sepsis-associated immunologic derangements. In this minireview, we present an overview of the recent advances in membrane-camouflaged biomimetic NPs, highlighting their multifaceted immunomodulatory effects in sepsis such as anti-infection, vaccination, inflammation control, reversing of immunosuppression, and targeted delivery of immunomodulatory agents.